Women's rights & resolutions from unofficial bodies - Great Britain Home Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1939)
Typescript submissions from non government bodies to the Home Office in relation to the League of Nations' inquiry into the status of women. Annotated with Government responses